PKM Kelompok Petambak Udang Dalam Upaya Memantau dan Menjaga Kualitas Tambak di Kecamatan Mlonggo Kabupaten Jepara - Buang Budi Wahono; Dias Prihatmoko; Luky Mudiarti (University of Islam Malang, 2019)
Gumuk Mas and Udang Lestari is a group of shrimp farmers in the Kec. Mlonggo Kab. Jepara. in checking water quality still uses traditional methods, namely by seeing the shrimp floating on the surface of the pond. if there is, the shrimp lacks oxygen, is prone to disease and will interfere with its breeding. when approaching the harvest time the shrimp farmers turn on the waterwheel continuously every day so that the shrimp does not lack DO (Dissolved Oxygen), even if the waterwheel continues then it will result in excess DO and wasteful electricity. Therefore we need a solution for checking water quality and waterwheel control. this activity proposes two main activities, namely training and farm management skills well related to monitoring and control of Dissolved Oxygen. this activity so that shrimp farmers can monitor the quality of shrimp pond water at any time. if water quality is lacking or exceeds the limit, prevention activities can be carried out as soon as possible and can increase crop yields and the welfare of shrimp farmers